Neferine and lianzixin extracts have protective effects on undifferentiated caffeine-damaged PC12 cells - Jingjing Chen; Mimi Tang; Manhua Liu; Yueping Jiang; Bin Liu; Shao Liu (BMC Complementary Medicine and Therapies, 2020)
Abstract Background The embryos of Nelumbo nucifera Gaertn seeds, lianzixin, are used in China as food and traditional herbal medicine. Principal therapeutic indications are insomnia, anxiety and pyrexia. Caffeine is a psychostimulant and excessive use predisposes to cell damage and neurotoxicity. We aimed to investigate the potential protect effect of Neferine and lianzixin extracts on undifferentiated caffeine-damaged phaeochromocytoma cells (PC12 cells). Methods A cell damage model based on undifferentiated PC12 was established with caffeine. Effect of Lianzixin extracts (total alkaloids, alcohol extract and water extract) and neferine on caffeine-damaged PC12 cells was evaluated. Cell viability was assessed using the methyl thiazolyl tetrazolium (MTT) assay, cellular morphology by inverted microscope, the nucleus by Hoechst 33342 staining and cleaved poly ADP-ribose polymerase (PARP) expression by western blot analysis. Results Lianzixin extracts (total alkaloids, alcohol extract and water extract) and neferine improved the viability of PC12 cells damaged by caffeine. The morphology of PC12 cells pretreated with neferine, or alcohol or water extract of lianzixin aggregated and attached better than caffeine-damaged cells, but cells pretreated with total alkaloids of lianzixin showed abnormal morphology. Compared with caffeine-damaged cells, cells pretreated with neferine, or alcohol or water extract of lianzixin showed a notable increase in nucleus staining and an obvious decrease in cleaved PARP expression. Conclusions Lianzixin extracts and neferine have protective effects against caffeine-induced damage in PC12 cells, which laid a foundation for finding a new medicine value of Lianzixin.